Depiction of Lakulisa in padmasana - Temples of India Project Team (Jio Institute, 2024)
The lintel of the sanctum-doorway features a depiction of Lakulisa in padmasana (lotus pose) with two arms, displaying dhyanmudra (the hand seal gesture for mediation). In his left hand, he holds a lakuta (club), while his right-hand grasps a fruit, as per his standard iconography. The image is housed inside a niche on the lalatabimba (lintel). On either side of the lintel, there are depictions of four-armed Brahma on the left and four-armed Vishnu on the right. This substitution of Shiva’s image with Lakulisa at the lintel niches of the sanctum doorway was once a common feature of the Pashupata tradition.